(untitled) (Indian Journal of Public Health Research & Development, 2023)
Introduction: Contraceptive choice is a critical component of women’s reproductive health and rights. In contrast the social and economic correlates of contraceptive use are less well understood, particularly in low and middles income countries, where contraceptive use if often assessed in the contest of maternal and child health interventions. Objectives: To study the Awareness about the contraceptive methods, to understand the practice of contraception regarding contraception & to find the Myths and Taboos regarding contraception among working population. Methodology: This study was conducted among all working women belonging to the age group of 20-49 years in northern district of Karnataka state, using a pre-validated questionnaire which was used to assess the awareness and practices of contraception among working women. Results: Among the total 2000 women taken into the study only 1409 participants participated in the study from that we observed that majority of them around 81.3% participants belonged to rural area, with 50.8% having a minimum graduate educational qualification & belonged to the age group of 20-29 years. They were aware of many factors about contraception such as the facilities where is it available the pros and cons associated with it but the association of disturbed cycles, its affectability to future pregnancy and weight gain were not known. Most of the women who practiced contraception commonly used condoms followed by permanent method of sterilization. Many women and their partners have the belief that contraception is associated with various side effects and hence they step back from using the various methods of contraception available to them. Conclusion: the working women had awareness regarding the facilities where they could approach for contraception, the advantage of preventing sexually transmitted diseases and so on. But they needed better education of the various types of methods of contraception available to them and the best option they can choose.